The miR-216/miR-217 Cluster Regulates Lipid Metabolism in Laying Hens With Fatty Liver Syndrome via PPAR/SREBP Signaling Pathway - Zhu, Lihui; Liao, Rongrong; Huang, Jiwen; Yan, Huaxiang; Xiao, Changfeng; Yang, Yunzhou; Wang, Huiying; Yang, Changsuo (Frontiers in Veterinary Science, 2022)
Fatty liver syndrome (FLS), a common metabolic disease in laying hens, caused by excessive hepatic fat deposition is a bottleneck in the poultry industry. However, no specific therapeutic methods have been developed. Evidence suggests that microRNAs (miRNAs) are essential for liver lipid metabolism and homeostasis, providing strong evidence for targeting miRNAs as a potential treatment option for liver diseases. However, the roles of miRNAs in the pathogenesis of FLS remain unclear. In present study, RNA-sequencing was performed to discern the expression patterns of miRNAs in normal and fatty livers of laying hens. In total, 12 dysregulated miRNAs (2 down-regulated and 10 up-regulated) were detected between the normal and fatty livers. Functional enrichment analysis showed the potential impacts of the dysregulated miRNAs on lipid metabolism. Notably, miR-216a/b and miR-217-5p, which belong to the miR-216/miR-217 cluster, were up-regulated in the sera and livers of FLS chickens, as well as free fatty acid (FFA)-induced LMH cells. Oil-red O staining revealed that up-regulation of the miR-216/miR-217 cluster induced lipid accumulation in FFA-induced LMH cells. Furthermore, the dual luciferase gene reporter assay and RT-qPCR analysis demonstrated that 3-hydroxyacyl-CoA dehydratase 2, F-box protein 8, and transmembrane 9 superfamily member 3 (TM9SF3) were directly targeted by miR-216a/b and miR-217-5p, respectively, and suppressed in the fatty livers of laying hens. Moreover, overexpression of the miR-216/miR-217 cluster or reduction in TM9SF3 levels led to activation of the proliferator-activated receptor/sterol regulatory-element binding protein (PPAR/SREBP) pathway. Overall, these results demonstrate that the miR-216/miR-217 cluster regulates lipid metabolism in laying hens with FLS, which should prove helpful in the development of new interventional strategies.